Long-term trends in water quality and influence of water recharge and climate on the water quality of brackish-water lakes: A case study of Shahu Lake. (15th December 2020) - Tian, Linfeng; Zhu, Xiang; Wang, Longmian; Du, Peng; Peng, Fuquan; Pang, Qingqing
Abstract: This study aimed to assess the long-term fluctuations in water quality and the influence of Yellow River water recharge and climatic condition on the water environmental index of a typical brackish-water lake. This study investigated several surface water quality parameters and their relationships with the water quality index (WQI) and trophic status index (TSI) of Shahu Lake from 2011 to 2018. A health risk assessment was conducted, and the correlations among water recharge, climatic conditions, and the aforementioned elements were determined. Results show that the water quality in this lake went from good to moderate and back to good as reflected in the changes in its WQI values from 2011 to 2018. The relative water quality inferiority of this lake in 2015 and 2016 was attributed to the significant increase in its CODMn, TP, TN, NH3 –N, and fluoride (F − ) concentrations during these years. A combination of these parameters could rapidly predict water quality through a stepwise multiple linear regression. During the study period (except in the frozen season), Shahu Lake maintained a eutrophic status every month (especially in July) irrespective of the spatial changes resulting from low secchi depth and high TP. The limiting nutrient of Shahu Lake changed from phosphorus to both nitrogen and phosphorus, especially during summer, due to seasonal variations and exogenous inputs. The lake had an acceptable health risk level, and water recharge both had positive and negative effects on this lake as reflected in the significant decrease or increase in the concentrations of its principal parameters. This condition was also attributed to temperature and precipitation, which resulted in significant TSI variations. The findings of this study provide ways of estimating and forecasting water quality and trophic status and a basis for managing and improving similar brackish-water lakes. Highlights: Annual WQI in good or moderate state, annual TSI in eutrophic status of Shahu Lake. F −, CODMn, TP, TN, NH3 –N were the main indexes to predict water quality. The values of HI and CR were within the acceptable risk levels. Water recharge significantly increased TP, F −, CODMn, and WQI but decreased chl-a. TSI had significant relationships with air temperature and precipitation. Graphical abstract: Image 1